2020
DOI: 10.3390/joitmc6040161
|View full text |Cite
|
Sign up to set email alerts
|

Dissecting Tether’s Nonlinear Dynamics during Covid-19

Abstract: The present study is on the five cryptocurrency daily mean return time series linearity dynamics during the Covid-19 period. These cryptocurrencies were chosen based on their influence on the market, primarily driven by its market capitalisation. Tether is included as the most important stable coin on the market, nominally pegged to the U.S. dollar (USD). The reason to investigate it is that there are some inconsistencies in its behaviour as opposed to the other four cryptocurrencies. This study found that the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 47 publications
0
7
0
Order By: Relevance
“…Given the growing interest in Bitcoin, it is important to choose a reliable model to forecast the risk of such an investment. By using specifications that can account for structural breaks in GARCH, namely Markov switching GARCH models, the authors of [20] analyzed Bitcoin daily log returns exhibiting regime changes in their volatility dynamics. Because of such dynamics, it is important to explore ways to reduce the level of risk of an investment in Bitcoin and to hedge or discover some factors that can influence the price movement of Bitcoin.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…Given the growing interest in Bitcoin, it is important to choose a reliable model to forecast the risk of such an investment. By using specifications that can account for structural breaks in GARCH, namely Markov switching GARCH models, the authors of [20] analyzed Bitcoin daily log returns exhibiting regime changes in their volatility dynamics. Because of such dynamics, it is important to explore ways to reduce the level of risk of an investment in Bitcoin and to hedge or discover some factors that can influence the price movement of Bitcoin.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…All the return series are non-normal as the Jarque-Bera test highly rejects the null of normality, thus justifying the application of the NARDL model, which considers that nonlinearity is due to short-and long-run effects and also due to positive and negative changes. Further, Maiti et al (2020) mentioned about the nonlinearity of the daily return of Tether cryptocurrency. The relationship between these two markets is expected not to be linear because while the crypto markets are unregulated, the stock markets across the world are regulated.…”
Section: Datamentioning
confidence: 99%
“…However, Tether was a safe haven during the Covid-19 pandemic. It was the most stable cryptocurrency because it was pegged with U.S. dollar (Maiti et al, 2020). Nasreen et al (2021) examined the interconnection and enclosed opportunities from September 30, 2015, to June 04, 2020, of the top 9 cryptocurrencies where TVP-VAR showed a high degree of interrelatedness.…”
Section: Review Of Literaturementioning
confidence: 99%
“…Further, they discussed the functioning of the Oracles technology used in blockchain. Maiti et al (2020) examined the behavior of five cryptocurrencies chosen based on the market influence during covid-19 with the help of threshold autoregression (TAR) and Smooth transition autoregressive (STAR) model. They found that Tether's behavior was inconsistent with the other four because the daily average time series pattern was non-linear while linear in the case of the other four.…”
Section: Review Of Literaturementioning
confidence: 99%